2009
DOI: 10.1016/j.toxlet.2008.09.003
|View full text |Cite
|
Sign up to set email alerts
|

Review and pooled analysis of studies on MTHFR C677T polymorphism and esophageal cancer

Abstract: Esophageal cancer has been associated with tobacco and alcohol consumption, gastric reflux, exposure to nitrosamines from food or other environmental sources, and diets lacking folate. Susceptibility to esophageal cancer may be modified by functional polymorphisms in genes along the folate metabolic pathway, such as methylenetetrahydrofolate reductase (MTHFR). The C677T polymorphism is the most common functional variant, leading to a reduction in enzyme activity. We report a pooled analysis of 5 studies on the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
30
1
4

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(39 citation statements)
references
References 50 publications
4
30
1
4
Order By: Relevance
“…20 The potential associations between MTHFR genotype status and a number of medical complications have been evaluated using methodologies such as case-control, cohort, Mendelian randomization, and meta-analysis. A modest positive association has been found between the MTHFR "thermolabile" polymorphism and many different medical complications, including, but not limited to, thromboembolic disease (in non-North-American populations only), 21,22 stroke, [23][24][25][26][27] aneurysm, 28 peripheral artery disease, 29 migraine, 30 hypertension, 31,32 recurrent pregnancy loss, 33,34 male infertility, 35,36 risk for offspring with neural tube defects, 37,38 certain cancers, [39][40][41] neuropsychiatric disease, 42 and chemotherapy toxicity. 43,44 …”
mentioning
confidence: 99%
“…20 The potential associations between MTHFR genotype status and a number of medical complications have been evaluated using methodologies such as case-control, cohort, Mendelian randomization, and meta-analysis. A modest positive association has been found between the MTHFR "thermolabile" polymorphism and many different medical complications, including, but not limited to, thromboembolic disease (in non-North-American populations only), 21,22 stroke, [23][24][25][26][27] aneurysm, 28 peripheral artery disease, 29 migraine, 30 hypertension, 31,32 recurrent pregnancy loss, 33,34 male infertility, 35,36 risk for offspring with neural tube defects, 37,38 certain cancers, [39][40][41] neuropsychiatric disease, 42 and chemotherapy toxicity. 43,44 …”
mentioning
confidence: 99%
“…Such change would disturb the homeostasis of folate metabolism, which was believed to be associated with the occurrence and development of several chronic diseases. Systematic reviews and meta-analysis revealed the MTHFR SNP C677T could increase the risk of developing schizophrenia, congenital heart defects, esophageal cancer, gastric cancer and breast cancer (Lewis et al, 2005;Langevin et al, 2009;Dong et al, 2010;Zhang et al, 2010;Yin et al, 2012) while probably playing as a preventive factor against colorectal cancer and children acute lymphoblastic leukemia (Hubner et al, 2007;Taioli et al, 2009;Yan et al, 2012). There were also many studies concerning the association between prostate cancer risk and SNP C677T, however, no conclusiveness was achieved: Heijmans (Heijmans et al, 2003) suggested MTHFR SNP C677T be a risk factor of prostate cancer in Dutch population, but HSI-CHIN WU found the polymorphism conferred a significant decreased risk of the disease; moreover, some studies showed no statistical relationship between them (Stevens et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…The homozygote and heterozygote of 667T exhibit a 30 and 65% activity, respectively, compared with the 100% activity exhibited by the 677CC genotype (73). Previous case-control studies and meta-analyses have revealed that the MTHFR C677T allele increased the risk of developing ESCC (74)(75)(76)(77)(78). In coordination with ADLH2*2, individuals with C677T demonstrated elevated ORs (74).…”
Section: Interactions Between Alcohol Consumption and The Correspondimentioning
confidence: 99%